Weeds interference per nutrient in carrots grown with or without black oat mulch - CRISTINA LANG, MICHELE; DE ARAÚJO BARBOSA , JAQUELINE; DOUGLAS FERREIRA , SILVIO; REGINA GODOY BAPTISTÃO, AMANDA; VILANOVA DA COSTA , NEUMARCIO (Comunicata Scientiae, 2023)
The interaction with weeds jeopardizes the nutrients accumulation in the carrots’ plants. The mulch can reduce competition effects and provide advantages to the cultivation. This research aimed to assess the black oat (Avena strigosa Schreb.) hay mulch effect on dry matter accumulation of weeds and nutrients (N, P, K, and S) accumulation in the carrots plants cultivar “Alvorada.” The experiments were set during the crop seasons 2016/2017 and 2017/2018 in a randomized-block design with a factorial scheme 2 x 5, with five repetitions. The first factor corresponded to soil cover (with or without mulch), and the second factor, to the interaction time with weeds (0, 15, 30, 60, and 120 days after emergence). The interaction with the weed community reduced nutrients absorption and dry matter accumulation in the roots of the carrot’s plants. Interference with nutrients absorption was more intense in crops without black oat hay mulch than with mulch. Mulch can reduce weeds’ dry mass by 75.6% during the entire culture cycle. Therefore black oak oat mulch reduces the weed interference allowing higher nutrients accumulation and roots biomass in the carrots plants cultivar “Alvorada.”